Atomic imaging of mechanically induced topological transition of ferroelectric vortices - Pan Chen (Nature Portfolio, 2020)
Controlling topological polar vortices promises to open up new applications for ferroelectric materials. Here, the authors proposed a method to mechanically manipulate polar vortices and monitored the transition between vortex and ferroelectric phase by in-situ scanning transmission electron microscopy.